Hanging: A Ten-Year Retrospective Review of Malaysian Forensic Cases - SZ, Md Naziri; SN, Abu Bakar; A, Alias; A, Ibrahim; DMJ, Mohamed Swarhib; F, Mohd Nor (IIUM Medical Journal Malaysia, 2020)
Introduction: Hanging is one of the most common methods of suicide in Malaysia, and to date, there is a rise in the number of deaths by hanging among adults. The purpose of this study was to determine the pattern of hanging in Malaysia from the year 2000 till 2009. Methods: The sample comprised 108 cases received at the Universiti Kebangsaan Malaysia Medical Centre, and five parameters, namely, age, sex, racial affiliation, marital status, and medical history were studied. Results: Of the 108 cases, 56% was reported to be Chinese. Suicide by hanging was more predominant in males (81%), and a high number of cases were seen in age groups of 21 to 30, 31 to 40 and 41 to 50 years. Of the cases studied, half of them were married, and previous history of physical and mental illness and alcohol intoxication were reported. Conclusions: In brief, this data would help the higher authorities in detecting the causes of suicide by hanging, as well as detecting the high risk groups with suicidal tendencies. In this way, suicide can be prevented and thus, the rate of suicide by hanging could be reduced in Malaysian.